2014 Spillover Report. (Policy Papers; Policy Paper ;, 2014)
Global spillovers have entered a new phase. With crisis-related spillovers and risks fading, changing growth patterns are the main source of spillovers in the global economy at this juncture. Two key trends are highly relevant here. First, signs of self-sustaining recovery in some advanced economies indicate that the unwinding of exceptional monetary accommodation will proceed and lead to a tightening of global financial conditions in the coming years. An uneven recovery, though, suggests normalization will proceed at different times in different countries, with possible spillover implications. Second, growth in emerging markets is slowing on a broad basis since its precrisis peak and can carry noticeable spillover effects at the global level. Model code and programs used for the spillover simulations can be made available. Data used for the empirical analysis can be made available unless restricted by copyright or confidentiality issues.